Diversitas Kapang Serasah Daun Talok (Muntingia calabura L.) Di Kawasan Desa Sukolilo Barat, Kecamatan Labang, Kabupaten Bangkalan, Madur - Miranti, Arum Krisna; Rukmi, MG Isworo; Suprihadi, Agung (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Leaf litter is one kind of substrate which is good for mold’s growth because of its organic matters content particularly cellulose. Research on mold diversity on Talok (Muntingia calabura L.) leaf litter which grow abundance at Sukolilo Barat Village, Labang Subdistrict, Bangkalan, Madura was conducted in order to determined the diversity and to isolate xerophilic mold as well as to examined the enzymatic activity of the isolates. The isolation has been done by direct and indirect method on DG18 agar, MEA, and OA from three samples which is taken purposively. The enzyme activities observed were cellulolytic, amylolitic and proteolytic at 310C temperature. The results showed that 24 isolates found were come from 3 genus i.e. Aspergillus, Curvularia and Fusarium. The Aspergillus was the largest number found. The Shannon-Wiener Index of Diversity showed that the diversity of three leaf litter samples categorized medium. The highest cellulolytic, amylolitic and proteolytic activity at 310C incubation were showed by A. tamarii (ISM 1), A.aculeatus (ISM 10) , A. terreus sp. 3 (ISM 17) respectively. Keywords : Diversity, mold, talok litter leaf, Madura